AN ANALYSIS OF THE TRANSLATION OF IDIOMATIC PHRASAL VERBS IN A NOVEL ENTITLEDTHE SANDS OF TIMEWRITTEN BY SIDNEY SHELDON - Eka Firmansyah, - (2008)
In this paper, the writer discusses idiomatic phrasal verbs as a part of everyday speech. In general, we often find this kind of idioms in films, fiction books (novel and short story), lyrical songs, and so on. Sometimes, it is not easy to understand the meaning of idiomatic phrasal verbs. Besides, they have their own meanings, which cannot be translated word-for-word. The descriptive qualitative method incorporated in this study allowed the writer to make a systematic and accurate description about the acquired data. The acquired data were all the idiomatic phrasal verbs found in the novel of which a hundred of them were taken using a quota sampling method. From the research findings, three types of idiomatic phrasal verbs were discovered in the novel. They were classified based on Brown's constructions. They are the transitive-separable idiomatic phrasal verbs, transitive-inseparable idiomatic phrasal verbs, and intransitive-inseparable idiomatic phrasal verbs. It is also apparent in the novel that transitive-separable idiomatic phrasal verbs were the most frequent type of phrasal verbs used in the novel. In accordance with Baker's translation strategies, paraphrase strategy is the most frequent translation strategy applied by the translator to translate idiomatic phrasal verbs. The other three kinds of translation strategies used are translation by using an idiom of similar meaning but dissimilar form, translation by omission and translation by using an idiom of similar meaning and similar form.